Providing Institutional Support for Academic Engagement in Online and Blended Learning Programs - Sara Tuiloma; Charles R. Graham; Adriana María Martinez Arias; Diana Maria Parra Caicedo (MDPI AG, 2022)
In this paper, we examine how universities can evaluate the level of support they provide to help their students with affective, behavioral, and cognitive engagement in their online and blended learning experiences. Additionally, it identifies what types of supports help students engage academically and what barriers hinder their online engagement. Using a survey instrument sent to university students (n = 1295), we conducted a mixed-methods analysis to understand better how students feel the institution supports their online engagement and what barriers they experience. To accomplish this, we addressed the following research questions: (1) How do students feel the institution supports their academic engagement for online and blended learning (including affective, behavioral, and cognitive dimensions)? and (2) What are the barriers to student academic engagement for online and blended learning at the institutional level? We used the Academic Communities of Engagement (ACE) framework as a lens for understanding the types of support institutions should provide in online and blended learning programs. While our descriptive statistics revealed that students might not distinguish the types of support they receive, the qualitative findings suggested they need more behavioral support. Our results also showed that 31% of students reported they experienced three or more barriers to their learning, which should be addressed when considering institutional support elements.